Melatonin Rhythm and Its Relation to Sleep and Circadian Parameters in Children and Adolescents With Autism Spectrum Disorder - Martinez-Cayuelas, Elena; Gavela-Pérez, Teresa; Rodrigo-Moreno, María; Merino-Andreu, Milagros; Vales-Villamarín, Claudia; Pérez-Nadador, Iris; Garcés, Carmen; Soriano-Guillén, Leandro (Frontiers in Neurology, 2022)
Introduction: Sleep problems are prevalent among individuals with autism spectrum disorder (ASD) and a role has been attributed to melatonin in this multifactorial comorbidity. Methods: A cross-sectional study was conducted including 41 children and adolescents with ASD (9.9 ± 3.02) and 24 children and adolescent with normal intellectual functioning (8.42 ± 2.43) used as controls. Subjects were matched for sex, body mass index and pubertal staging, and all were drug-naïve. Circadian and sleep parameters were studied using an ambulatory circadian monitoring (ACM) device and saliva samples were collected around the onset of sleep allowed to determine dim light melatonin onset (DLMO). Results: Prepubertal individuals with ASD presented later DLMO and an earlier decline in melatonin during adolescence. A relationship was found between melatonin and both sleep and circadian parameters. Patients and controls with later DLMOs were more likely to have delayed sleep onset times. In the ASD group, subjects with later daytime midpoint of temperature had a later DLMO. Later melatonin peak time and DLMO time were related to lower general motor activity and lower stability of its rhythms. Conclusion: Melatonin secretion pattern was different in individuals with ASD and it showed a relationship with sleep and circadian parameters. Alterations in DLMO have not been previously reported in ASD; however, high variability in study design and sample characteristics prevent direct comparison. The ACM device enabled measurement of circadian rhythm, a scarcely described parameter in children with ASD. When studied in combination with other measures such as melatonin, ACM can offer further knowledge on sleep problems in ASD.